Amyloid and Tau Positron Emission Tomography in Suggested Diabetes-related Dementia - Takenoshita, Naoto; Fukasawa, Raita; Ogawa, Yusuke; Shimizu, Soichiro; Umahara, Takahiko; Ishii, Kenji; Shimada, Hitoshi; Higuchi, Makoto; Suhara, Tetsuya; Hanyu, Haruo (Current Alzheimer Research, 2018)
Background: Type 2 diabetes mellitus (DM) has been shown to increase the risk for cognitive decline and dementia, such as Alzheimer disease (AD) and vascular dementia (VaD). In addition to AD and VaD, there may be a dementia subgroup associated with specific DM-related metabolic abnormalities rather than AD pathology or cerebrovascular disease, referred to as diabetes-related dementia (DrD). Method: We studied 11C-PiB and 11C-PBB3 positron emission tomography (PET) in 31 subjects with DrD and 5 subjects with AD associated with DM to assess amyloid and tau deposits in the brain. Results: All subjects with AD showed both positive PiB and PBB3. However, only 12 out of 31 subjects (39%) with DrD showed positive PiB, whereas 17 out of 21 subjects (81%) who underwent PBB3 PET showed positive PBB3. Depending on the positivity of PiB and PBB3, we classified 21 subjects into a negative PiB and a positive PBB3 pattern (11 cases, 52%), indicating tauopathy, a positive PiB and a positive PBB3 pattern (6 cases, 29%), indicating AD pathology, or a negative PiB and a negative PBB3 pattern (4 cases, 19%). Among 11 subjects showing a negative PiB and a positive PBB3 pattern, there were 2 PBB3 deposit patterns, including the medial temporal lobe only and extensive neocortex beyond the medial temporal lobe. Conclusion: DrD showed variable amyloid and tau accumulation patterns in the brain. DrD may be associated predominantly with tau pathology, in addition to AD pathology and non-amyloid/non-tau neuronal damage due to DM-related metabolic abnormalities.
Keywords: positron emission tomography